Hubungan Tingkat Kecemasan dengan Kualitas Tidur pada Mahasiswa Tahap Pre-Klinik dalam Menghadapi Ujian Blok di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Ni Made Aninda Febriyanti; Putu Asih Primatanti; Ni Luh Putu Eka Kartika Sari (Aesculapius Medical Journal, 2023)
Anxiety is a mental problem that is often experienced by medical students which can be interpreted as feeling worried and unable to perform obligations. The academic obligations that medical students have to perform such as block exams encountered are the initial triggers for anxiety that affect sleep quality. Sustained anxiety will affect the quality of student sleep, resulting in impaired physiological and psychological balance. This research aims to analyze the correlation between anxiety level and sleep quality of pre-clinical students when facing block exams in the Faculty of Medicine and Health Science of Warmadewa University. This research applied analytical study design using cross-sectional approach. The sampling technique was using proportional random sampling approach. The sample of the research covered 227 students of medical education. The instruments of this research were Hamilton Anxiety Rating Scale (HARS) dan Pittsburgh Sleep Quality Index (PSQI). The data analysis techniques employed within this research were univariate and bivariate analyses using the Rank Spearman test. The result of the analysis shows that out of the 227 samples; 146 respondents (64.3) indicated no anxiety, 44 respondents (19.4%) indicated mild anxiety, 19 respondents (9.3%) indicated moderate anxiety, and 14 respondents indicated (6.2%) severe anxiety. In terms of sleep quality; 67 respondents (29.5%) indicated good sleep quality and 160 respondents (70.5%) indicated poor sleep quality. The results of the Rank Spearman test analysis showed the value of p = 0.006 which means that p<0.05. So it can be concluded that there is a significant correlation between anxiety level and sleep quality of pre-clinical students when facing block exams.